School administrators' and teachers' level of awareness, interests and practices in learning culture - Lin, Normah; Mohd Ali, Hairuddin (2013)
Learning culture in school plays a vital role in boosting learning to students. School administrators and teachers are the front line who facilitates the school with learning culture. This study aims to evaluate the level of awareness, interests and practices between school administrators and teachers in promoting learning culture in school. A cross-sectional survey design was conducted in four schools and data were collected from 210 respondents. Specifically, the study focused on teachers in Kuala Lumpur and they were asked about learning culture. A questionnaire with 41 items (excluding demographic questions) was designed. Each respondent is requested to indicate his experience and perceptions on learning culture using DLOQ instrument. It was indicated that these variables are statistically significant and there are correlation between level of interests, awareness and practices. At school level, it is found that the age of respondents strongly influence the learning culture. Finally, correlation among the level of awareness, interests and practices in learning culture was identified. The finding presents an original study which examined the school administrators‘ and teachers‘ level of awareness, interests and practices towards learning culture in school. Implications and recommendations for future improvement of learning culture were channeled to the appropriate authorities.